Cultura construtiva à luz do design territorial: a valorização de um saber tradicional na comunidade de Canelatiua localizada em Alcântara – MA - RÊGO, Fabiana Aquino de Moraes (2020)
This research deals with questions about the theme Constructive culture in the light of Territorial Design: the valorization of traditional knowledge in the community of Canelatiua located in Alcântara - MA, within the complex correlation of policies and external actions that suppose to promote development in rural communities and quilombolas. Actions that can lead to the process of eradicating traditional constructive know-how passed from generation to generation and that transmits culture and memory. The general objective of this work was to identify and analyze the perceptions of residents about the values attributed to constructive culture in a quilombola community in Alcântara through Territorial Design, based on the speeches and practices of these residents. Its outline is outlined from a series of theoretical conceptual reflections obtained through a literary review and whose main focus is to address the role of tradition in constructive culture and the impact of development on traditions. We make use of the Territorial Design methodology with the approximation of areas that contribute to the valorization of a traditional know-how, which in this case is a constructive culture that is the materialization of empirical constructive practices and sociocultural identities in a given space, experienced and lived in an accumulated period of time. Thus, the tools chosen were oral history and semi-structured interviews. Through the methodological basis chosen in a qualitative research with descriptive bias and, through an informal and observational approach, we compiled and analyzed the narratives and speeches obtained in the field. We conclude that, possibly, the eradication of traditional construction techniques with mud and adobe will occur in the community of Canelatiua, under the risk of losing a fundamental element of the cultural and territorial identity of a people. In this sense, we emphasize the importance of maintaining, in some way, the traditional constructive culture, which should not be lost or forgotten, as it strengthens the history, origin and memory of the community.